Unusual dominant genotype NIA1 of Enterocytozoon bieneusi in children in Southern Xinjiang, China. - Meng Qi; Fuchang Yu; Aiyun Zhao; Ying Zhang; Zilin Wei; Dongfang Li; Longxian Zhang (Public Library of Science (PLoS), 2020)
Enterocytozoon bieneusi is the mainly pathologies or intestinal disorders that causes approximately 90% of reported cases of human microsporidiosis. To understand the prevalence and genotype distribution of E. bieneusi in the Xinjiang Uygur Autonomous Region, China, 609 fecal samples were collected from children in kindergarten in Southern Xinjiang and screened for this pathogen by PCR and sequencing of the internal transcribed spacer (ITS). Thirty-six fecal samples (5.9%, 36/609) were positive for E. bieneusi, with the highest prevalence observed in children from Yopurga (17.5%, 11/63). Nine genotypes were identified, of which six were known (A, CHN6, D, EbpA, KB-1, and NIA1) and three were novel (CXJH1, CXJH2 and CXJH3). Genotype NIA1 was most prevalent (52.8%, 19/36), followed by genotypes D (16.7%, 6/36), A (8.3%, 3/36), and EbpA (8.3%, 3/36). The remaining five genotypes were detected in one sample each. Phylogenetic analysis revealed that the E. bieneusi isolates clustered into two groups, one consisting of six genotypes (Group 1: A, CXJH1, D, EbpA, KB-1, and NIA1) and another consisting of three genotypes (Group 2: CHN6, CXJH2, and CXJH3). Our results confirmed that infection of E. bieneusi unusual dominant genotype NIA1 occurs in children in Xinjiang, China. Further epidemiological studies must be conducted to clarify potential sources of E. bieneusi infection in this area.